Katherine Dunham: Black Educator, Artistic Force, and Underrecognized Figure in Adult Education - Misti Galvan (Adult Education Research Conference, 2025)
Katherine Dunham, 20th century Black dance educator and scholar has not been included in the history of Adult Education. This paper contends that she deserves discussion and inclusion in AE.
Keywords: Black Adult Education; dance; writing; culture; arts